Changes in supervised drug-injecting practices following a community-based educational intervention: A longitudinal analysis. (1st November 2018) - Mezaache, Salim; Protopopescu, Camélia; Debrus, Marie; Morel, Stéphane; Mora, Marion; Suzan-Monti, Marie; Rojas Castro, Daniel; Carrieri, Patrizia; Roux, Perrine
Highlights: Unsafe injecting practices are associated with infectious and non-infectious diseases. This educational intervention seems to be effective in reducing unsafe practices. It affects hygiene practices, the use of sterile equipment and injecting technique. This intervention needs to be evaluated in different contexts. Abstract: Background: People who inject drugs face several health issues because of unsafe injecting practices. We aimed to evaluate changes in supervised drug-injecting practices following the implementation of a face-to-face educational intervention. Methods: The national study ANRS-AERLI was conducted in 17 harm reduction (HR) facilities in France between 2011 and 2013. Eight offered the intervention and nine did not. We conducted a pre-post analysis focusing on injecting practices data, collected in the 8 HR facilities providing the intervention. The intervention consisted of providing face-to-face educational sessions including direct observation of injecting practices, counseling about safer injecting, and shared discussion. Injecting practices were collected following a checklist and classified as safe or unsafe. To assess changes in injecting practices, practices were compared before (at baseline) and after at least one educational session. Findings: Mixed logistic models showed that the 78 participants included were more likely to improve in the following drug-use steps: setting up a clean preparation area (Adjusted Odds Ratio (AOR) = 3.4, 95% Confidence Interval (95% CI) = 1.6–7.6), hand washing (AOR = 7.2, 95% CI = 3.1–16.4), skin cleaning (AOR = 5.6, 95% CI = 2.5–12.1), choice of safe injection site (AOR = 6.5, 95% CI = 1.5–28.8) and post-injection bleeding management (AOR = 12.8, 95% CI = 5.5–29.9). Furthermore, participants were less likely to lick their needles before injecting (AOR = 8.1, 95% CI = 1.5–43.4) and to perform booting/flushing (AOR = 2.5, 95% CI = 1.2–5.3). Conclusions: The AERLI intervention seems to be effective in increasing safe drug-injecting practices.